Construction and comprehensive analysis of the biological network related to rheumatoid arthritis‐related interstitial lung disease. (19th October 2022) - Zhou, Wei; Ma, Xianghui; Jia, Xiaodong; Zheng, Juan; Yan, Lili; Fu, Yanfa
Abstract: Objective: Interstitial lung disease (ILD) is a severe manifestation of rheumatoid arthritis (RA), which is characterized by low survival time post‐diagnosis. Thus, it is important to explore the role of gene regulation related with ILD. Method: Constructed a RA‐ILD‐related long chain noncoding RNA – messenger RNA (lncRNA‐mRNA) network (ILD‐LMN), based on ILD‐ and RA‐related genes. We analyzed the topological properties of the resulting network. Result: The results for network modularization and functional analysis showed that ILD‐LMN performed basic and specific functions in ILD pathology. Furthermore, differential expression and correlation analysis of hub nodes revealed highly correlated competitive endogenous RNA regulatory relationships with important roles in pathological regulation. Following this, statistical analysis of disease‐related single nucleotide polymorphisms (SNPs) in hub lncRNAs revealed that some of transcription factor‐related SNPs were significantly associated with the expression of lncRNA. In fact, these SNPs exhibited significant differential expression in disease and normal samples. Conclusion: These results suggest that ILD‐LMN has important implications in the study of disease. Altogether, the study of RA‐ and ILD‐related lncRNA and genes on the basis of biological network would assist in providing better treatment opportunities for ILD patients. Additionally, it would promote further research on treatment of the disease.